Stress Cardiomyopathy with an "Inverse" Takotsubo Pattern in a Patient with Acute Aneurysmal Subarachnoid Hemorrhage. Issue 8 (6th June 2013) - Waller, Christine J.; Vandenberg, Byron; Hasan, David; Kumar, Avinash B.
<x xml:space="preserve">Abstract</x> Background Subarachnoid hemorrhage (SAH) induced myocardial dysfunction (often labeled neurogenic stunned myocardium) encompasses a spectrum of clinical presentations ranging from an isolated elevation of cardiac enzymes to cardiogenic shock. Objective We describe a case of stress cardiomyopathy in a patient following acute aneurysmal subarachnoid hemorrhage that showed an "inverse" or reverse takotsubo pattern on echocardiography. Case Report The patient was a 46‐year‐old female who presented with acute cardiogenic shock following acute subarachnoid hemorrhage necessitating aggressive cardiorespiratory in the ICU. Her admission echo showed a depressed left ventricular ejection fraction of 25%. The basal 2/3 of the left ventricle (LV) was severely hypokinetic and the apical 1/3 of the LV was hypercontractile, i.e. the reverse or inverse takotsubo pattern of regional wall motion abnormality. With ongoing aggressive support her cardiovascular function steadily improved and on day 6 her follow up echo showed LV ejection fraction increased to 60–65% with resolution of the previous regional wall motion abnormality. The patient was discharged to a neuro‐rehabilitation facility on day 16. Summary The "inverse" or "reverse" takotsubo pattern of regional wall motion abnormalities, i.e. with preserved apical LV contractility and hypokinesis of the basal walls of the LV is more common in patients following acute SAH.